Are the Analgesic Effects of Morphine Added to Transversus Abdominis Plane Block Systemic or Regional? A Randomized Clinical Trial - Meryem Onay; Osman Kaya; Elçin Telli; Ayten Bilir; Mehmet Sacit Güleç (Pain Research and Management)
Trial Registration: ClinicalTrials.gov identifier: NCT05420337